2013
DOI: 10.1128/jcm.00509-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification by 16S rRNA Gene Sequencing of an Actinomyces hongkongensis Isolate Recovered from a Patient with Pelvic Actinomycosis

Abstract: A case of Actinomyces hongkongensis pelvic actinomycosis in an adult woman is described. Conventional phenotypic tests failed to identify the Gram-positive bacillus isolated from a fluid aspirate of a pelvic abscess. The bacterium was identified by 16S rRNA gene sequencing and analysis using the SmartGene Integrated Database Network System software.A 47-year-old, gravida 2, para 2, immunocompetent woman presented to the hospital with pelvic pain and fever 13 days after a total abdominal hysterectomy and salpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…The importance of Actinomyces spp. in gynecological surgical-site infections is further supported by two other recent reports of pelvic abscesses, one after TVOR (Actinomyces israelii) and another after total abdominal hysterectomy and salpingectomy (Actinomyces hongkongensis) (7,8).…”
supporting
confidence: 62%
“…The importance of Actinomyces spp. in gynecological surgical-site infections is further supported by two other recent reports of pelvic abscesses, one after TVOR (Actinomyces israelii) and another after total abdominal hysterectomy and salpingectomy (Actinomyces hongkongensis) (7,8).…”
supporting
confidence: 62%
“…This risk was explained by the production of a biofilm by the Actinomyces that prevents the toxicity effect of the copper and reduces the efficacy of antibiotics [21]. In our study, for those patients who had never used an IUD, we found a context of immunodepression and gynecological or digestive surgery, as described previously [11,22].…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, A. odontolyticus (126) and some of the more recently isolated Actinomyces species, including A. urogenitalis (127,128), A. hongkongensis (129,130), A. cardiffensis (65), and A. turicensis (131,132), appear to play a role in IUCD-associated pelvic actinomycosis. Certain gynecologic procedures may predispose an individual to complications with Actinomyces organisms; a case of bacteremia from a tubo-ovarian abscess caused by A. urogenitalis in a non-IUCD user exposed to a transvaginal oocyte retrieval procedure was reported (128), while in IUCD users, a similar procedure resulted in an infectious complication with A. israelii (124), and another gynecologic procedure, hysterectomy and salpingectomy, resulted in pelvic actinomycosis due to A. hongkongensis (129). In fact, the type strain of A. hongkongensis originates from a pus specimen from a pelvic actinomycosis case where ovarian tubes were described as being filled with pus (130).…”
Section: Abdominal/pelvic Actinomycosismentioning
confidence: 99%